Checklist of the family Chloropidae (Diptera) of Finland - Nartshuk, Emilia (Pensoft Publishers, 2014)
Abstract. A checklist of 147 species the Chloropidae (Diptera) recorded from Finland. Centorisoma elegantulum Becker is recorded for the first time from Finland.